Pengabdian Kapada Masyarakat Melalui Kuliah Kerja Nyata (KKN) Di Desa Tutul Kecamatan Balung Kabupaten Jember - Ricky Jamil; Muhammad Wildan Habibi; Bahrul Rizal; Risma Wati Ramli; Muhammad Ali Fakih; Najma Adis Putri Midani; Intan Ainur Rohmah; Shavrila Gita Puspita Sari; Aura Tesalonika Hendriardani; Serly Putri Yunitasari; Indah Tri Wahyuni; Imam Wahyudi; Restu Arif Purnomo (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Community service through the Community Service Program (Kuliah Kerja Nyata/KKN) is one form of student contribution in addressing problems within the community. This study aims to examine the role of KKN in improving the village economy and providing education to children and the community in Tutul Village, Jember Regency. The methods used in this study are socialization and direct observation. KKN students participated in activities such as creating promotional videos and company logos, conducting counseling on the dangers ofearly marriage and stunting, and educating school children about the risks of online game addiction. The results show that through KKN activities, students can have a positive impact by increasing community awareness of social and economic issues, as well as supporting the development of village potential through business promotion and health and social education.